Pengaruh Latar Belakang pada Pengucapan Dialek Jawa dalam Film “Yowis Ben” Karya Bayu Skak - Dea Sholihatun Ni’mah; Anik Fatiatur Rohmaniyah; Binti Tsaniatul Wakhidah; Muhammad Yusron Yusuf; Luthfa Nugrahaini (STIKes Ibnu Sina Ajibarang, 2025)
This study examines how the actors’ linguistic backgrounds influence the pronunciation of Javanese dialect in Bayu Skak’s film Yowis Ben. Using a phonetic-phonological approach and performative analysis, this study explores how non-native Javanese actors pronounce typical Javanese dialect sounds in the context of film acting. Data were obtained through transcriptions of conversations in the film and observations of the actors’ performances, then analyzed to reveal the forms of phonological variation that emerged. The findings indicate that individual linguistic factors of the actors play an important role in determining the authenticity of dialect pronunciation. Non-Javanese actors tend to show symptoms of phonological interference, such as phoneme changes and intonation that do not conform to Javanese dialect patterns. However, intensive dialect training can help some actors approach more authentic pronunciation. The uniqueness of this study lies in its approach that combines phonological studies with performance analysis in films, and its focus on the use of dialect in cinematic contexts, not just everyday or formal communication. This study makes a significant contribution to the development of applied phonology and offers insights for the film industry that promotes local cultural values